Hannibal - Harris, Thomas, 1940- (New York, N.Y. : Delacorte Press, 1999)
Seven years after his escape from the authorities, Hannibal Lecter, a serial killer, is tracked down by one of his former victims using FBI agent Clarice Starling as bait.
Sequel to: The silence of the lambs.
Keywords: Serial murderers -- Fiction; Fugitives from justice -- Fiction; Government investigators -- Fiction; Revenge -- Fiction; Lecter, Hannibal (Fictitious character); Psychological fiction